2018
DOI: 10.1017/s0950268818003023
|View full text |Cite
|
Sign up to set email alerts
|

Sexual risk behaviour in a cohort of HIV-negative and HIV-positive Rwandan women

Abstract: Here we wanted to assess whether sexual risk behaviour differs dependent by human immunodeficiency virus (HIV) status by following 100 HIV− and 137 HIV+ women recruited at two university teaching hospitals in Rwanda. Women were tested for sexually transmitted infections (STIs; trichomoniasis, syphilis, hepatitis B and C) and for reproductive tract infections (RTIs; candidiasis, bacterial vaginosis (BV)) and were interviewed at baseline and 9 months later. BV was the most prevalent infection, while syphilis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Previous diagnosis of other STDs and lack of knowledge of oneʼs own hepatitis status were also associated with risks of HIV infection among a small group of donors. While the latter might indicate lack of routine health care, previous diagnosis of other STDs is reported by multiple studies as a good indicator of high‐risk sexual behaviors . These results, combined with our findings about significant risks associated with MSM, multiple concurrent sex partners, having remunerated sex, and inconsistent use of condoms, highlight the importance of enhanced effort in educating the public on HIV transmission risks and the importance of safe sex practice in China.…”
Section: Discussionsupporting
confidence: 70%
“…Previous diagnosis of other STDs and lack of knowledge of oneʼs own hepatitis status were also associated with risks of HIV infection among a small group of donors. While the latter might indicate lack of routine health care, previous diagnosis of other STDs is reported by multiple studies as a good indicator of high‐risk sexual behaviors . These results, combined with our findings about significant risks associated with MSM, multiple concurrent sex partners, having remunerated sex, and inconsistent use of condoms, highlight the importance of enhanced effort in educating the public on HIV transmission risks and the importance of safe sex practice in China.…”
Section: Discussionsupporting
confidence: 70%
“…As the number of cases of individual STIs and RTIs was low, we did not attempt to stratify individual RTIs and STIs in the binary logistic regression analysis. However, as we showed in our previous studies , more unmarried than married women were HIV positive and differences in the prevalence of STIs and RTIs between HIV‐positive and HIV‐negative women exist, which may partly explain why being married was retained as an independent predictive factor for LSIL. Studies show that the risk of cervical cancer increases with the duration of use of oral contraceptives .…”
Section: Discussionmentioning
confidence: 69%
“…While Rwandan women generally reported having had only a few lifetime sexual partners , the number of HPV infections was high, particularly among HIV‐positive women. In our previous study , we also showed that other STIs, besides HIV infection, were common among HIV‐positive women even if they claimed to have used condoms during sexual activity or claimed not to have been engaged in sexual activity. A high rate of reported condom use among HIV‐positive individuals but a high rate of new STIs has also been demonstrated in other African countries .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…HIV-infected individuals through sexual route exhibited higher plasma HIV load and lower CD4 + T cell counts compared with those infected by blood transmission, resulting in a faster progression to AIDS among those infected by the sexual route [20]. Furthermore, HIV-infected individuals who were infected through sexual transmission may on the other hand have an increased risk of acquiring human papillomavirus, syphilis, candidiasis, herpes and genital ulcer disease [21, 22].…”
Section: Discussionmentioning
confidence: 99%